Why Men Are Afraid of Women - Camoin, FranCois (Book collections on Project MUSE., 1984)
The tie that binds men and women, that makes men do absurd things that they will very likely be sorry for later, is at the center of this prize-winning collection of stories. There is, for example, Jack Segal, who is thirty-six and who owns a record store on Ocean Boulevard in Santa Monica and who has fallen in love-badly and madly in love-with the fourteen-yearold daughter of his friend Katzman. Segal can't think. He eats, but it doesn't taste like anything. He drives the freeways, floats above the city lights, and finds himself almost wishing that the Great Quake would come and solve everyth.